2023
DOI: 10.1021/acsaem.2c02992
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Triple-Phase Interface in PEMFC by Proton Conductor Absorption on the Pt Catalyst

Abstract: In a proton exchange membrane fuel cell (PEMFC), the membrane electrode assembly (MEA) is the core component and the region of the oxidation−reduction. In order to obtain a great performance, Pt with excellent catalyst efficiency is usually adopted in PEMFC as the catalyst. However, the high cost and poor durability remain the two major challenges in the application of PEMFC; thus, it is worth paying attention to enhance the utilization of the Pt catalyst and the stability of PEMFC. In this work, the Nafion ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The choice of Nafion array height at 1.5 μm is based on three reasons. First, our previous works have shown that fuel cells with a cone Nafion array height of 1.3 μm exhibit optimal performance in both the anode and cathode. , Second, we optimized the fuel cells performance with different Nafion array heights under a constant diameter of 400 nm and found that the fuel cell with an array height of 1.5 μm obtains optimal performance when the height of the Nafion array varies from 0.5 to 2.5 μm (Figure S7). Third, to focus on the effect of Nafion array size ( i .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The choice of Nafion array height at 1.5 μm is based on three reasons. First, our previous works have shown that fuel cells with a cone Nafion array height of 1.3 μm exhibit optimal performance in both the anode and cathode. , Second, we optimized the fuel cells performance with different Nafion array heights under a constant diameter of 400 nm and found that the fuel cell with an array height of 1.5 μm obtains optimal performance when the height of the Nafion array varies from 0.5 to 2.5 μm (Figure S7). Third, to focus on the effect of Nafion array size ( i .…”
Section: Resultsmentioning
confidence: 96%
“…The accumulation of hydrogen becomes difficult to vent and can cause a highpressure hydrogen bulge on the surface, leading to damage to the 3 μm exhibit optimal performance in both the anode and cathode. 48,49 Second, we optimized the fuel cells performance with different Nafion array heights under a constant diameter of 400 nm and found that the fuel cell with an array height of 1.5 μm obtains optimal performance when the height of the Nafion array varies from 0.5 to 2.5 μm (Figure S7). Third, to focus on the effect of Nafion array size (i.e., the diameter of the Nafion pillar), the height of the Nafion array was maintained at 1.5 μm, while the diameter of the Nafion pillars was varied.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 However, the sluggish kinetics of the halfcell reaction is a significant challenge in improving the performance of fuel cell devices. 3 Catalysts play a critical role in overcoming this challenge by lowering the activation energy barrier of the oxygen reduction reaction (ORR). Although Ptbased materials remain the most practical catalysts for the ORR, the high cost and scarcity of Pt hinder its widespread application in fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel cells are a promising technology for generating clean and efficient energy. , However, the sluggish kinetics of the half-cell reaction is a significant challenge in improving the performance of fuel cell devices . Catalysts play a critical role in overcoming this challenge by lowering the activation energy barrier of the oxygen reduction reaction (ORR).…”
Section: Introductionmentioning
confidence: 99%
“…Proton exchange membrane fuel cell (PEMFC) is the most promising fuel cell because it can start quickly, work at low temperature, and output a high power density. Gas diffusion layer (GDL) is one of the key components of PEMFC, , as it can transfer electrons from the catalyst layer to the bipolar plates, allow the reactant gases to reach the catalyst through it for electrochemical reaction, and remove the excess water produced at the cathode side. GDL is composed of a gas diffusion substrate and a microporous layer (MPL). , MPL provides support to the catalyst layer, adjusts the pore structure of GDL, and reduces the contact resistance between the catalyst layer and gas diffusion substrate. …”
Section: Introductionmentioning
confidence: 99%